A positive Selection Escherichia Coli Recombinant Protein Expression Vector for One-Step Cloning - James, Shinto; Jain, Vikas (Frontiers in Bioengineering and Biotechnology, 2022)
We introduce OLIVAR (Orientation seLection of Insert in Vector through Antisense Reporter) as a novel selection strategy for the insertion of protein-coding genes into vector backbones. As a proof-of-concept, we have engineered a plasmid vector, pGRASS (GFP Reporter from Antisense promoter-based Screening System), for gene cloning in E. coli. With pGRASS, positive clones can be effortlessly distinguished from negative clones after blunt-end cloning. The vector not only screens clones with an insert but also for its correct orientation. The design further allows for the expression of recombinant protein from the T7 promoter in an appropriate host bacterium. With this vector, we are able to reduce the entire cloning workflow into a single step involving a two-hour reaction at room temperature. We believe that our cloning-cum-screening system presented here is extremely cost-effective and straightforward and can be applied to other vector systems and domains such as phage display and library construction.